2020
DOI: 10.1186/s13063-020-04787-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental perspectives long term after neonatal clinical trial participation: a survey

Abstract: Background Although recruiting newborns is ethically challenging, clinical trials remain essential to improve neonatal care. There is a lack of empirical data on the parental perspectives following participation of their neonate in a clinical trial, especially at long term. The objective of this study is to assess experiences and emotions of parents, long term after trial participation in an interventional drug trial. Methods Parents of former participants of five neonatal interventional drug trials were sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Like our study, others have reported that lower education level is associated with higher study satisfaction [ 3 , 8 ]. Being part of a longitudinal study with visits several times per year provides a parent with an opportunity to ask questions and talk to professionals about the child’s type 1 diabetes risk.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Like our study, others have reported that lower education level is associated with higher study satisfaction [ 3 , 8 ]. Being part of a longitudinal study with visits several times per year provides a parent with an opportunity to ask questions and talk to professionals about the child’s type 1 diabetes risk.…”
Section: Discussionsupporting
confidence: 79%
“…Studies examining factors associated with parent study satisfaction are also limited. Less educated parents and those from racial or ethnic minority groups often report greater satisfaction than higher educated parents or those from the majority culture [ 3 , 8 ]. Higher overall satisfaction was also associated with fewer transportation problems and fewer study-related financial difficulties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is considered important that parents are continuously educated about the study details and their rights ( 8 ). When long-term contact is established between parents and the research team via an eIC system, it could help to remind parents of their child's participation in a research study, which may be forgotten ( 45 ). As formulated by the interviewed HCPs, it could be up to the parents to indicate how they would like to receive information.…”
Section: Discussionmentioning
confidence: 99%